Mujer y violencia: Interacciones temáticas en Delirio de Laura Restrepo - Bustamante Bustamante, Fanny Maritza (2024)
The goal of this research is to analyze the interactions in the thematic representations of women and violence in the soap operas: Delirio by Laura Restrepo, y Bruna; Soroche y los tios by Alicia Yanez Cossio, that represent a direct criticism of feminism to the patriarchal system. The methodology is based in a qualitative focus, so it is based in a descriptive and documental study. The analyzed literary works are constituted for the novelistic works mentioned previously. The following methods were used in the analysis and interpretation of the data: analytic-synthetic, inductive-deductive, and hermeneutic. The technique used in the analysis was designed and applied literary and thematic analysis sheets based in the pholiphony proposed for Bajtin. The results of the research concluded that the interactions between the woman and the violence en Delirio and, Bruna, soroche y los tios are established in the topics of identity, perception, consequences, types of violence, strategies, empowerment, and liberation realized by the feminine actors. At the same time, the research showed evidence that violence awakens a woman’s determination to take the decision to put a stop to the discrimination that she is being a victim of since men had use of reason and understanding and seeks to liberate herself definitely of the patriarchal yoke that differs humans, providing superiority to the masculine gender.